2013
DOI: 10.1080/17408989.2013.788145
|View full text |Cite
|
Sign up to set email alerts
|

Assessment as pedagogy: a consideration of pedagogical work and the preparation of kinesiology professionals

Abstract: Background: Assessment is a central feature of institutional education practices, including those in the higher education learning field of kinesiology. To optimise the valuable and desired outcomes of assessment and minimise its unintended and unhelpful outcomes, a comprehensive understanding of the assessment process is necessary. To date a comprehensive understanding of the assessment process has been missing within the professional and academic learning setting of kinesiology. Purpose: To better understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 37 publications
(56 reference statements)
0
24
0
6
Order By: Relevance
“…The framework applied in the study was identified given its potential to address the twin challenges of quality and equity that impact the overwhelming majority of classrooms within the South African schooling sector (Frempong et al 2011). Firstly, the framework postulates formative assessment as both a tool and a process to enhance pedagogical practices (Hay, Tinning & Engstrom 2015;Wiliam 2011a). Secondly, the effective use of formative assessment has the potential to create more opportunities that support all learners within the classroom, including those with diverse needs and experiences (Black & Wiliam 2009;Kalinec-Craig 2017;Pryor 2011).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The framework applied in the study was identified given its potential to address the twin challenges of quality and equity that impact the overwhelming majority of classrooms within the South African schooling sector (Frempong et al 2011). Firstly, the framework postulates formative assessment as both a tool and a process to enhance pedagogical practices (Hay, Tinning & Engstrom 2015;Wiliam 2011a). Secondly, the effective use of formative assessment has the potential to create more opportunities that support all learners within the classroom, including those with diverse needs and experiences (Black & Wiliam 2009;Kalinec-Craig 2017;Pryor 2011).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…These practices include how teachers introduce lessons, the questions teachers ask and the opportunities provided for learners to respond, the tasks and activities that teachers set and the support provided for learners to engage with these tasks and activities, the classroom climate that teachers seek to create, the types of learning that teachers seek to promote as well as the types of assessments applied and the manner in which teachers use assessment information for identifying and addressing the specific learning needs of their learners (Alexander 2008;Megahedet al 2008;Schweisfurth 2011;Westbrook et al 2013). Hay et al (2015) note that the relationship between assessment and pedagogy has been most overtly articulated through the AfL (or formative assessment) approach. The authors argue that the 'fundamental premise is that assessment provides teachers with information on the progress of their learners' learning so that appropriate adjustments in pedagogy and curriculum can be made to optimise future learning' (p. 8).…”
Section: Formative Assessment and Pedagogical Practicementioning
confidence: 99%
“…O entendimento que a inclusão da avaliação na instrução tem um forte impacto na melhoria do envolvimento assim como da aprendizagem dos alunos (Wiliam & Leahy, 2015) e, consequentemente, aporta melhorias na qualidade e eficácia das aulas . Por sua vez, Hay e Penney ( 2009) argumentam que a avaliação de alta qualidade (alto valor formativo) pode ter um impacto positivo no currículo e na pedagogia, munindo os professores de informações que lhes permite analisar e adaptar o seu processo de ensino-aprendizagem para atender às necessidades dos alunos (Stiggins & Chappuis, 2011), dando-lhes maiores possibilidades de alcançar os resultados de aprendizagem Hay, Tinning, & Engstrom, 2015). Os professores precisam de saber bem o que querem que os seus alunos alcancem a fim de definirem como irão avaliar e ensinar (Stiggins & Chappuis, 2011).…”
Section: O Que Sabemos?unclassified
“…Além disso, os professores têm de garantir que os critérios de avaliação estão alinhados com as intenções de aprendizagem definidas para os seus alunos (Annerstedt & Larsson, 2010) e que os critérios de avaliação são claros e conhecidos pelo professor e alunos, desde o início da unidade de ensino . Atendendo a este cenário e indo de encontro ao panorama internacional, que tem sido de uma menor concentração nos testes e um maior foco na função formativa da avaliação, depreende-se que a avaliação deve ser usada como uma necessidade pedagógica, isto é, como meio de promover aprendizagens e experiências significativas para os alunos (Black & Wiliam, 1998;Boud, 2007;Hay et al, 2015). Neste quadro de debate educacional, a noção de que a avaliação deve ser encarada como a promoção da aprendizagem tem vindo a ganhar crescente destaque (Boud, 2007).…”
Section: O Que Sabemos?unclassified
“…Paralelamente, é necessário haver: (1) um alinhamento entre avaliação, currículo e pedagogia, (Penney et al, 2009); (2) uma avaliação contínua orientada para o alcance das intenções de aprendizagem ; (3) uma recolha e o uso de evidências que permitam atender às necessidades dos alunos ; (4) uma valorização das contribuições dos alunos durante o processo de avaliação por meio da auto e heteroavaliação (Falchikov, 2005); e (5) uma definição clara e partilhada com os alunos das intenções de aprendizagem e dos critérios de avaliação (Wiliam & Thompson, 2008). Avaliação, currículo e pedagogia devem, assim, funcionar em total concordância (Hay et al, 2015;Penney et al, 2009), conforme descrito por Wiggins e McTighe (1998), através do conceito 'backward design', no qual sugerem 'começar pelo fim', definindo primeiro os objetivos, depois como avaliar a aprendizagem e, por fim, ensinar as estratégias a serem usadas. A definição do currículo deve ocorrer numa relação dinâmica com a definição do desenho das tarefas de aprendizagem e de avaliação (MacPhail, Tannehill, & Karp, 2013) -passagem de um alinhamento linear entre currículo, pedagogia e avaliação, marcado pela sequencialidade, para um alinhamento integrado em que o currículo, as tarefas e a avaliação -aula após aula -, estão em constante interação.…”
Section: Para Onde Queremos Caminhar?unclassified